Expression of Noggin and Gremlin1 and its implications in fine‐tuning BMP activities in mouse cartilage tissues. Issue 8 (8th November 2016) - Yu, Xiaodan; Kawakami, Hiroko; Tahara, Naoyuki; Olmer, Merissa; Hayashi, Shinichi; Akiyama, Ryutaro; Bagchi, Anindya; Lotz, Martin; Kawakami, Yasuhiko
ABSTRACT: Increasing evidence supports the idea that bone morphogenetic proteins (BMPs) regulate cartilage maintenance in the adult skeleton. The aim of this study is to obtain insight into the regulation of BMP activities in the adult skeletal system. We analyzed expression of Noggin and Gremlin1, BMP antagonists that are known to regulate embryonic skeletal development, in the adult skeletal system by Noggin‐LacZ and Gremlin1‐LacZ knockin reporter mouse lines. Both reporters are expressed in the adult skeleton in a largely overlapping manner with some distinct patterns. Both are detected in the articular cartilage, pubic symphysis, facet joint in the vertebrae, and intervertebral disk, suggesting that they regulate BMP activities in these tissues. In a surgically induced knee osteoarthritis model in mice, expression of Noggin mRNA was lost from the articular cartilage, which correlated with loss of BMP2/4 and pSMAD1/5/8, an indicator of active BMP signaling. Both reporters are also expressed in the sterna and rib cartilage, suggesting an extensive role of BMP antagonism in adult cartilage tissue. Moreover, Noggin‐LacZ was detected in sutures in the skull and broadly in the nasal cartilage, while Gremlin1‐LacZ exhibits a weaker and more restricted expression domain in the nasal cartilage. These results suggest broad regulation of BMP activities by Noggin and Gremlin1 in cartilage tissues in the adult skeleton, and that BMP signaling and its antagonism by NOGGIN play a role in osteoarthritis development. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1671–1682, 2017.